Overview of Services and Characteristics of Pregnant Mothers in the Era of the Covid-19 Pandemic in Bpm Pera Clinic in 2022 - R. Oktaviance Oktaviance; Risda Mariana Manik; Bernadetta Ambarita; Charolina Moriana Sipakkar (Institute of Computer Science (IOCS), 2022)
Based on the centeres for Disease Control and Prevention report, pregnant women who are positive for Covid-19 are at higher risk for premature birth (delivery od babies earlier than 37 weeks) and stillbirths. In addition, pregnant women who are positive for Covid-19 are also at a higher risk of developing other pregnancy complications. The problem of psychlogical disorders often occurs during the pregnancy proces, both in the first, second and third trimesters, Covid-19 causes various clinical manifestations, especially in pregnant women, because pregnant women are a high risk group for contracting the Covid-19 virus. The sampling technique is a accidental sampling. The sample in this study are 31 pregnant women. The results show that the characteristics based on the service of the respondents almost all experienced a fairly good change in service (90.3%), the characteristics based on the respondent’s education most of them have high school education (70.9%), the characteristics based on the respondent’s exposure are mostly working (64.5%), the characteristics are based on age most respondent’s are aged 20-29 years (45.1%), the characteristics based on parity of respondent’s are mostly multiparous parity (45.2%). Conclusion the level of education, type of work, gestasional age, and parity of pregnant women have a very important distribution in influencing services and characteristics of pregnant women in the future pandemic Covid-19.